Stres Kerja terhadap Kepuasan Kerja pada Pengemudi Gojek Salatiga selama Pandemi COVID-19 - Bagaskoro Bayuaji (Psyche 165 Journal, 2021)
The purpose of this study is to examine the impact of job stress on job satisfaction among Gojek online drivers in Salatiga. The number of participants in this study was 50 that data collected by using questionnaire with Incidental Sampling technique. This study used a quantitative approach with simple linear regression data analysis. The results showed that there was a significant negative impact between job stress on job satisfaction among Gojek online drivers in Salatiga with -2,053 t-value (t-value -2,053> t-table 2,009) and 0,045 significance value (Sig.<0,05). These results indicated that the higher job stress among Gojek online drivers, the lower would be job satisfaction among them. Keywords: job stress, job satisfaction, online drivers, pandemy, covid-19.